Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3389/fcell.2017.00041
|View full text |Cite
|
Sign up to set email alerts
|

How Cells Can Control Their Size by Pumping Ions

Abstract: The ability of all cells to set and regulate their size is a fundamental aspect of cellular physiology. It has been known for sometime but not widely so, that size stability in animal cells is dependent upon the operation of the sodium pump, through the so-called pump-leak mechanism (Tosteson and Hoffman, 1960). Impermeant molecules in cells establish an unstable osmotic condition, the Donnan effect, which is counteracted by the operation of the sodium pump, creating an asymmetry in the distribution of Na+ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
87
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 67 publications
2
87
0
Order By: Relevance
“…4A,[A]i = 155 mM). Analytically, it can be shown that the number of moles of X 304 determines completely the volume of the compartment, while the permeant ions alone cannot be 305 used to predict steady state volume(Kay, 2017). Similarly, all initial impermeant anion concentrations 306 resulted in identical steady state values of ECl (-83.8 mV), EK (-95.1 mV) and Vm (-72.6 mV) (Fig.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…4A,[A]i = 155 mM). Analytically, it can be shown that the number of moles of X 304 determines completely the volume of the compartment, while the permeant ions alone cannot be 305 used to predict steady state volume(Kay, 2017). Similarly, all initial impermeant anion concentrations 306 resulted in identical steady state values of ECl (-83.8 mV), EK (-95.1 mV) and Vm (-72.6 mV) (Fig.…”
mentioning
confidence: 96%
“…Our theoretical approach is based on the pump-612 leak formulation (Tosteson and Hoffman, 1960). It suggests that mammalian cells maintain their 613 volume under osmotic stress generated by impermeant anions and the Donnan effect by employing 614 active transport of Na + and K + using the Na + /K + -ATPase (Armstrong, 2003;Kay, 2017). A Donnan 615 equilibrium, a true thermodynamic equilibrium requiring no energy to maintain it, is not possible in 616 cells with pliant membranes like neurons (Sperelakis, 2012).…”
mentioning
confidence: 99%
“…IMFs can arise from selective transport or differential permeability to charged molecules, or can be generated through membrane-bound redox reactions of the respiratory chain [3,4]. A key point to recognize is that IMF and MP are coupled to each other and further to cell volume and metabolism [17,18]. The connection to volume arises from the distribution of ions and charged molecules (essential for the formation of MP), determining also the osmotic forces on cells [17].…”
Section: Bioelectrical Nature Of the Cellmentioning
confidence: 99%
“…A key point to recognize is that IMF and MP are coupled to each other and further to cell volume and metabolism [17,18]. The connection to volume arises from the distribution of ions and charged molecules (essential for the formation of MP), determining also the osmotic forces on cells [17]. The connection to metabolism is achieved by four general mechanisms (figure 2b).…”
Section: Bioelectrical Nature Of the Cellmentioning
confidence: 99%
“…Thus, cells observe all the requirements for Gibbs-Donnan disequilibrium and they are under pressure to swell. The reason they maintain their volume is because they use cellular energy to fuel the Na + /K + -pump to constantly fight the leak of ions and the influx of water (Kay, 2017; Tosteson & Hoffman, 1960). The pump basically renders the membrane “impermeable” to Na + by actively extruding the Na + that enters the cell through leak pathways.…”
Section: Cell Volume Homeostasismentioning
confidence: 99%